A Comprehensive Overview of Stress, Resilience, and Neuroplasticity Mechanisms - Buenrostro-Jáuregui, Mario Humberto; Muñóz-Sánchez, Sinuhé; Rojas-Hernández, Jorge; Alonso-Orozco, Adriana Ixel; Vega-Flores, German; Tapia-de-Jesús, Alejandro; Leal-Galicia, Perla (International Journal of Molecular Sciences, 2026)
Stress is a core concept in the mental health field that expands upon the seminal definition of stress as an acute response to the disruption of homeostasis. Stress is a complex process that involves both environmental challenges and the triggering of internal responses and impacts physiological, psychological, and behavioral systems. The capacity of the human brain to cope with stress is particularly crucial in early life, when neurodevelopment is highly plastic. Early-life stress (ELS), defined as exposure to severe chronic stress during sensitive periods of development, has been shown to cause lasting changes in brain structure and function. However, not all individuals exposed to ELS develop pathological outcomes, suggesting the presence of resilience mechanisms: adaptive processes that allow an individual to cope with adverse situations while maintaining psychological and neurobiological health. The aim of this review was to synthesize recent advances in the understanding of the neuroplasticity mechanisms underlying resilience to ELS. We discussed the neurobiological pathways implicated in stress response and adaptation, including the roles of neurogenesis, synaptic plasticity, and neural circuit remodeling. By focusing on the interplay between stress-induced neuroplastic changes and resilience mechanisms, we aimed to provide insights into potential therapeutic targets for stressrelated psychopathology.
Keywords: stress resilience; neuroplasticity; early-life stress; allostatic load; adaptation